Monitoring the architecture of anionic κ-carrageenan/cationic glycine betaine amide surfactant assemblies by dilution: A multiscale approach. (2nd January 2017) - Gaillard, C.; Wang, Y.; Covis, R.; Vives, T.; Benoît, Maud; Benvegnu, T.
Graphical abstract: Highlights: ⿢ The dilution effect of κ-carrageenan/GB surfactant assemblies was investigated. ⿢ Singular hybrid surfactant/polysaccharide nano-, micro-objects were observed. ⿢ Dilution effect provided a gradual dissociation of assemblies nanostructure. Abstract: The interaction between glycine betaine-based cationic surfactant and algal polysaccharide κ-carrageenan was studied by investigating the dilution effect of the surfactant/polymer assemblies driven by electrostatic interactions. Two aqueous solutions of cationic surfactant and κ-carrageenan at two molar ratios (3.5 and 0.8) diluted with factors of 5 and 10 times, were tested by various analytical methods including a multiscale observation by Transmission Electron Microscopy (TEM) and Laser Scanning Confocal Microscopy (LSCM) to understand the solution behavior of surfactant and oppositely charged polymer at both nano- and micrometer scale. Raman spectroscopy as well as confocal Raman imaging were applied to give Supplementary information about the surfactant/polysaccharide interactions and the distribution of assemblies. These analyses confirmed the formation of singular hybrid surfactant/polymer nano-, microobjects and they revealed the influence of dilution on the nanostructures. These results give an insight of the mechanism of the dilution effect on surfactant/polymer assemblies that could be valuable in pharmaceutical formulations, food and cosmetics fields.